A continuous-time walking pattern generator for realizing seamless transition between flat-contact and heel-to-toe walking. (4th March 2023) - Tazaki, Yuichi; Hanasaki, Satomi; Yukizaki, Soh; Mitazono, Yugo; Nagano, Hikaru; Yokokohji, Yasuyoshi
Abstract : A planning algorithm that can generate continuous-time walking patterns including the seamless transition between flat-contact and heel-to-toe walking gaits is proposed. The planner makes use of the closed-form solution of a modified linear inverted pendulum mode which includes the ZMP and the weight ratio of each foot explicitly in its dynamics. The heel-to-toe movement of each foot is directly parameterized by the ZMP, and therefore consistency between the foot movement and the low-dimensional dynamics is ensured. In simulations with a 32 DoF model of a life-sized humanoid robot, fast human-like walking at the maximum speed of 4.6 km/h was achieved. GRAPHICAL ABSTRACT: UF0001